Analysis measurements of millet collision coefficient of restitution for mechanized seeding - Yifei Li; Wenqi Zhou; Shujuan Yi; Tao Chen; Dongming Zhang; Song Wang (PLoS ONE, 2025)
The millet collision coefficient of restitution (COR) is one of the important elementary physical parameters for researching the precision hole seeding system. In this study, to explore the factors affecting the bounce issue observed when seeds exit the seed-metering and seed-guiding devices, the dynamic equations for the millet collision process were derived employing Newtonian kinematics, and a COR measurement test bench was built. The effects of collision material type, speed and variety respectively on the COR were investigated by single-factor experiments and orthogonal experiments. Single-factor tests revealed that COR values decreased in the sequence of Acrylic plate, ABS, Rubber, Black soil,Meadow soil, and Sandy loam soil, with Tuogu exhibiting higher COR than Zhang Zagu 13 and Shuangyu, the latter having the lowest value. During two collision phases, the COR progressively decreased as seeding speed increased. Orthogonal tests identified the significant influences of each factor. A combination of bench and simulation tests validated the test results, showing no significant differences and confirming the method’s viability for determining COR. These findings offer a reference for optimizing the design of relevant components within the millet metering system.